2018
DOI: 10.1002/tafs.10074
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Genetic Structure in Phenotypic Spotted Bass in Texas

Abstract: Hybridization is common in fishes and can result in a wide range of outcomes. The capture of a world record phenotypic Guadalupe Bass Micropterus treculii raised questions about potential hybridization with Spotted Bass M. punctulatus. Subsequent, limited genetic sampling from the drainage (Colorado River) did not indicate hybridization in the world record sample or other phenotypic Guadalupe Bass, but phenotypic Spotted Bass produced unexpected genotypes. This called into question the assumed distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…S1 ). This observation is consistent with a study using Sanger-sequenced loci that detected Guadalupe Bass genes in specimens that were phenotypically identified as Spotted Bass 86 , highlighting that mismatch between phenotype and genotype for Spotted and Guadalupe basses in rivers of central Texas will be a challenge for the accurate species identification and conservation management of these populations.…”
Section: Resultssupporting
confidence: 88%
“…S1 ). This observation is consistent with a study using Sanger-sequenced loci that detected Guadalupe Bass genes in specimens that were phenotypically identified as Spotted Bass 86 , highlighting that mismatch between phenotype and genotype for Spotted and Guadalupe basses in rivers of central Texas will be a challenge for the accurate species identification and conservation management of these populations.…”
Section: Resultssupporting
confidence: 88%
“…The presence of Spotted and Guadalupe basses in Cedar Lakes is plausible, considering that Micropterus species are tolerant of oligohaline conditions (Peterson 1991; Peterson and Ross 1991; Lowe et al 2009; Norris et al 2010), other species of Micropterus (i.e., Largemouth Bass M. nigricans and Smallmouth Bass M. dolomieu ) have been captured by TPWD in other Texas estuaries, and, last, Guadalupe and Spotted basses are present in the Brazos River (Churchill and Bettoli 2015; Curtis et al 2015), which is geographically close to the study sites. Extensive hybridization and introgression has been documented in Texas among native (Largemouth Bass, Guadalupe Bass, Spotted Bass) and introduced (Florida Bass M. salmoides and Smallmouth Bass) Micropterus species (Whitmore and Hellier 1988; Morizot et al 1991; Lutz‐Carrillo et al 2006, 2018; Bean et al 2013). Therefore, it is possible that we detected presence of hybrid Micropterus bass rather than pure‐strain representatives of Spotted and Guadalupe basses, which demonstrates one limitation of eDNA metabarcoding—the inability of the method to differentiate hybridized from pure‐strain populations.…”
Section: Discussionmentioning
confidence: 99%
“…Such high differentiation among river basins in Texas has been shown by previous ecological and genetic analyses of mussels and fish, which mussels need for large-scale dispersal during their parasitic larval stage on host fish. For example, Spotted Bass showed large genetic divergence between river basins ( Lutz-Carrillo et al, 2018 ), and mussel and fish community composition were also found to differ significantly between river basins of Texas ( Dascher et al, 2018 ). Yet, more studies of population subdivision among North American freshwater mussels and other aquatic species with distributions that span multiple basins that drain into the Gulf of Mexico ( e.g ., Bohn et al, 2023 ) are still critically needed, which we begin to address in this study.…”
Section: Discussionmentioning
confidence: 99%